(untitled) (Journal of the College of Basic Education, 2025)
The study aimed to design a set of rehabilitation exercises using different levels of resistance bands and variations in contraction types for men aged 40–45 years suffering from non-slipped lower back pain. It also sought to identify the effect of rehabilitation using different resistance band intensities and contraction type variations on strengthening the spiral line muscles and reducing non-slipped lower back pain in this age group, The study adopted an experimental methodology using a two-group design (experimental and control). The research population included men aged 40–45 years with non-slipped lower back pain who visited the Baghdad Teaching Hospital / Physical Therapy Department. The total number of patients was 15, and all of them were selected as the research sample using a comprehensive enumeration method (100% of the original population). In accordance with the experimental design requirements, they were divided into two groups: experimental and control, After preparing the research tests and designing the rehabilitation protocol using various levels of resistance bands and types of muscular contractions, the protocol was applied during the research trial. The results were processed using the SPSS system; the findings concluded that rehabilitation using varying intensities of resistance bands and different contraction types is suitable for sessions targeting spiral line muscle rehabilitation and reduction of non-slipped lower back pain in men aged 40–45 years. Its application helps in strengthening the spiral line muscles and reducing the severity of non-slipped lower back pain in the targeted age group, Recommendations emphasized the importance of considering the duration of muscle elongation fixation when using resistance bands of different levels, ensuring it is appropriate for the capabilities of patients with non-slipped lower back pain in the 40–45 age group, and avoiding overuse. It is also essential to apply the principles of progression, comprehensiveness, and individualization in rehabilitation to match the needs of the target group.